The Episcopal and Philippine Independent Churches concordat of full communion : revisited - Pinera, Wylan Rey (Quezon City : St. Andrew's Theological Seminary, 1990)
This paper is written to answer some mind buggling questions. It is the hope of the author that the readers will be enlightened on the historical aspect of the Concordat. The reason why the Concordat remained a strange agreement, especially in the grassroots level will hopefully be answered in this paper. The spirit of the Concordat was only felt during the first years of the relationship. Their problems arose which hampered the full implementation of its provisions. After 29 years, the Concordat is only remembered when September 22 comes. The Concordat then becomes a commemorative event in the church. The problems encountered by both churches contributed to the failure of the Concordat. However, we should not also discard the contributions that it gave to the IFI and Episcopal Church.
A degree paper presented to the faculty of St. Andrew's Theological Seminary
In partial fulfillment of the requirements leading to the degree of Bachelor in Theology
Thesis (B.Th.)-- St. Andrew's Theological Seminary